The Green Publicity State: Sustainability, Austerity, and the 'Green Economy' in Michigan and Ontario, 2007-2012 - Tombari, Stephanie L. (My University, 2016)
In Michigan and Ontario, the “green economy” has been touted by government as a “win-win” solution to reducing greenhouse gasses and replacing thousands of manufacturing jobs lost before and during the global financial crisis. Some scholars, however, argue that despite economic and climate crises, there is little new about the policies being rolled out in advanced industrialized states; instead, political elites adopted business-as-usual policies after 2009 that offer little hope for greater social, economic, or ecological sustainability. In this green “publicity state”, political elites engage as much, if not more, in the politics of environmental discourse than in policymaking for a greener, more sustainable society. This thesis thus explored the research questions: To what extent have policymakers in Ontario and Michigan evoked argumentative imperatives that neoliberal policies are the way to create green jobs, increase socio-economic equality, and/or halt climate change? To what degree can policies in Ontario and Michigan be classified as ‘sustainable’? Does the policy rhetoric match the policy reality? In what similar and different ways do public policies get framed, communicated, and constrained by underlying neoliberal understandings of the economy and state that then limit the policy options that governments see as possible? In what ways does this contribute to the naturalization of green neoliberalism? To answer these questions, we examined the public policies and political rhetoric of renewable energy in Michigan and Ontario under the administration of Governors Jennifer Granholm and Rick Snyder, and the Ontario Liberal government of Premier Dalton McGuinty between 2007 and 2012. The theoretical framework for this paper was constructed using Gramscian and critical discourse theories which maintain that ideological and economic hegemony manifests, and is constantly being reproduced, through political discourse. First, we conducted a comparative analysis of green economy policies, as well as a sample of additional social, economic, and fiscal policies that could contribute to greater or less sustainability in the two jurisdictions. These were then categorized according to a typology of green economy imaginaries. Second, Michigan State of the State speeches and radio addresses, and Ontario Budget speeches and Speeches from the Throne delivered during the period of study were analyzed using Fairclough and Fairclough’s (2012) critical discourse analysis for political argument. It was found that political elites construct imaginaries of the green economy using various argumentative claims in ways that often do not coincide with policies and/or policy outcomes. In this study, Granholm and McGuinty often used argumentative claims around renewable energy in ways that naturalize green neoliberal approach to sustainability, while greenwashing less ‘green’ policies; take credit for making their jurisdiction ‘greener’; deflect and assign blame for a shrinking economy; and position the green economy as a ‘win-win’ to unemployment and/or climate change. Despite labelling himself a “good, green Republican”, Governor Snyder did not engage in green economy policymaking or framing, instead pursuing a ‘classic’ neoliberal policy agenda. Furthermore, the arguments political elites are further constrained by both the existing economic regime and political institutions: a premier in a majority government has significantly more power to make bold argumentative claims and introduce policies than a state governor. This is evident in the fact that although their rhetoric around the green economy as a means to increasing jobs was similar, McGuinty was able to also frame the green economy as a means to reducing greenhouse gasses and introduce a bolder piece of renewable energy legislation than Granholm.
Keywords: public policy, green economy, Michigan, Ontario, austerity, publicity state